EVALUASI SARANA EVAKUASI KEBAKARAN DI KAWASAN PASAR MODERN (STUDY KASUS: SUZUYA MALL) - Rahmat Rizki Z; Mochammad Afifuddin; Abdul Munir (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2019)
Infrastructure development in Banda Aceh is experiencing a rapid increase, the occurrence of urbanization has its own impact on development. Construction of commercial buildings on a large scale makes the city of Banda Aceh even more beautiful. With the emergence of buildings that vary in demanding safety and security aspects of the building and the environment. Besides having a traditional market, Banda Aceh also has several modern markets namely Suzuya Mall, Hermes Mall and Matahari Store, and Pasar Atjeh New Building. In maintaining the comfort and tranquility of the community during the visit, it takes the safety of supporters inside the building. Various safety aspects exist, one of the most important aspects of safety that must be fulfilled by the building is the evacuation route. The methodology used mix methods between qualitative and quantitative while the number of samples used were 91 visitors and 64 employees. The result of primary data analysis from 10 (ten) variables explains that there are some variables whose interpretation of the score is small or categorized neutral with the meaning of the need for improvement such as the availability of exit (emergency exit) with the value of frequency index (FI) of 0.52; emergency door conditions with an FI value of 0.60; emergency lamp with FI value of 0,51; fire detector with an FI value of 0.50; disaster evacuation system with FI value of 0,51 and disaster management management with FI value equal to 0,50. The strategy that can be done based on the SWOT analysis is by establish Expert Staff who have been provided with education and training on disaster management; Compile Standard Operating Procedure (SOP) for disaster risk management; and Carry out regular short simulations / exercises.